The capBCA Locus is Required for Intracellular Growth of Francisella tularensis LVS - Zhang, Jing-Ren (Frontiers in Microbiology, 2011)
Francisella tularensis is the causative agent of tularemia and a category A bioterrorism agent. The molecular basis for the extreme virulence of Francisella tularensis remains unclear. Our recent study found that capBCA, three neighboring genes, are necessary for the infection of F. tularensis live vaccine strain (LVS) in a respiratory infection mouse model. We here show that the capBCA genes are necessary for in vivo growth of F. tularensis LVS in the lungs, spleens, and livers of BALB/c mice. Unmarked deletion of capBCA in type A strain Schu S4 resulted in significant attenuation in virulence although the level of the attenuation in Schu S4 was much less profound than in LVS. We further demonstrated that CapB protein is produced at a low level under the in vitro culture conditions, and capB alone is necessary for in vivo growth of F. tularensis LVS in the lungs of BALB/c mice. Finally, deletional mutations in capB alone or capBCA significantly impaired intracellular growth of F. tularensis LVS in cultured macrophages, thus suggesting that the capBCA genes are necessary for intracellular adaptation of F. tularensis. The requirement of this gene locus in intracellular adaption at least in part explains the significant attenuation of F. tularensis capBCA mutants in virulence.